ANALISIS BUKU AJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI SMP KELAS IX KURIKULUM 2013 (Studi Penerapan Pendekatan Saintifik Dan Muatan Multikultural Pada Materi Ajar) - Etika Nurmaya; Muhammad Hanif; Qurroti A'yun (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
This research is a literature study with a qualitative approach and uses the primary data source for Islamic Religious Education and Morals for Junior High School Class IX Curriculum 2013. With the content analysis method, it is found that there are five steps in the scientific approach, namely observing, questioning, associating, experiments, networking. However, in this textbook on Islamic Religious Education and Morals for Junior High School Class IX Curriculum 2013, the steps for the scientific approach are only observing, questioning and associating. Meanwhile experiment and networking are not applied in the book. The multicultural content in the book is only egalitarianism, tolerance, pluralism, help, humanity and social solidarity. The values of justice and deliberation are not contained in it. The stages of observing, questioning, associating is in the realm of knowledge, while experimenting and networking is in the realm of skills, the multicultural values in the book only reach the realm of knowledge, students only learn multicultural values, not continuing at the skill or skill stage. Application of these multicultural values.